2020
DOI: 10.1177/1090198120931443
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis of COVID-19 Outbreak in South Korea: A Common Challenge and Call for Action

Abstract: This study aims to analyze South Korea’s experience during the COVID-19 outbreak through a gendered lens. We briefly introduce the COVID-19 outbreak in Korea, scrutinize gendered vulnerability in contracting the virus, and then analyze the gendered aspects of the pandemic response in two phases: quarantine policy and mitigation policy. The authors elicit four lessons from the analysis. First, gender needs to be mainstreamed at all stages of a public health emergency response. Second, in addition to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…However, minor differences were observed. For example, females showed higher means and variability than males for the three factors (Kim et al, 2020). The variability of the three factors showed a mixed pattern.…”
Section: Resultsmentioning
confidence: 96%
“…However, minor differences were observed. For example, females showed higher means and variability than males for the three factors (Kim et al, 2020). The variability of the three factors showed a mixed pattern.…”
Section: Resultsmentioning
confidence: 96%
“…There has been a substantial call for attention to gender during the COVID-19 pandemic, reflecting a concern that responses to the pandemic that fail to consider gender differences and norms will be ineffective and uphold current gender and health inequalities (Wenham et al 2020). Researchers attending to gender have so far established that men are more likely to have severe outcomes from COVID-19 than women (Rabin 2020;Purdie et al 2020), women often occupy positions of high risk due to their overrepresentation in the healthcare sector, and there is an inadequate representation of women in health leadership and decision-making roles across the globe (Kim et al 2020;EIGE 2020). Being female and a nurse have both emerged as associated with a higher prevalence of depression and anxiety compared to other healthcare workers (Pappa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that depression and anxiety had increased in female nurses compared with other health workers 27 . According to studies focused on gender differences, it has been found that women usually work in high‐risk positions because of the high number of women in health‐related professions and women were insufficiently represented in the health sector in terms of roles of leadership and decision‐making worldwide 23,28–30 . Moreover, in certain gender studies conducted with nursing students before the Covid‐19 outbreak, it was reported that the attitudes of female students were more egalitarian when compared with male students and that nursing education had a positive effect on the “egalitarian attitude.” 31–33 In our study, it was found that the majority of the nursing students ( f = 11) had a nonegalitarian approach concerning gender roles (Figure 7).…”
Section: Discussionmentioning
confidence: 99%